1992
DOI: 10.1007/bf00012014
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of, and relationships between phosphorus and nitrogen concentration in shoot, stolon and root of white clover (Trifolium repens L.)

Abstract: Ninety eight white clover genotypes were cloned and grown in pots at two levels of phosphorus (P) supply in soil. After harvest the nitrogen (N) and P content of shoot (leaf, petiole and unrooted stolon), stolon and root tissue was determined. Broad sense heritabilities for %N, %P, and proportion of total N or P in each tissue type were calculated. Heritabilities ranged from 0.22 to 0.68. They were generally higher for %P than %N; and higher in shoot and stolon tissue than root tissue for %P, %N, and proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This shows that a moderately severe P stress was imposed . In agreement with other researchers we found that root growth was much less inhibited by P-stress than shoot growth (Caradus, 1992 ;Fageria et al ., 1988 ;Fredeen et al ., 1988: Lynch et al ., 1991 and root growth branching patterns appeared to be altered by plant P status . This was indicated by changes in dry weight allocation to fine versus thick roots ( Table 2) .…”
Section: Discussionsupporting
confidence: 82%
“…This shows that a moderately severe P stress was imposed . In agreement with other researchers we found that root growth was much less inhibited by P-stress than shoot growth (Caradus, 1992 ;Fageria et al ., 1988 ;Fredeen et al ., 1988: Lynch et al ., 1991 and root growth branching patterns appeared to be altered by plant P status . This was indicated by changes in dry weight allocation to fine versus thick roots ( Table 2) .…”
Section: Discussionsupporting
confidence: 82%